The characterization of the sphere of temperance in EN III.10 - Vasconcelos, Bernardo César Diniz Athayde (Revista Archai, 2018)
Our article deals with Aristotle’s account of the sphere of temperance (ÏƒÏ‰Ï†ÏÎ¿ÏƒÏÎ½Î·) in the Nicomachean Ethics. The goal is to provide a detailed analysis of NE III.10 in order to identify the difficulties this chapter presents us with and to introduce and discuss the interpretations set forth by the secondary literature. Of special interest to us are Aristotle’s intense dialogue with Plato; the difficulty in understanding touch as the most common of the senses and Aristotle’s severe judgment of the pleasures of the sphere of temperance. In short, Aristotle seems to set out from platonic thesis and notions only to distance himself from them by introducing his own, associating temperance with the most common of the senses, namely, the sense of touch. This association is not based, as it could seem prima facie, on a merely empirical observation but on the assumption that touch is the most fundamental and necessary sense for humans and animals alike. Temperance, therefore, as the excellence in the relation with the most fundamental and necessary of the senses, seems to be a pre-condition for rational action. From this Aristotle derives the etymology of the term, as the one who preserves practical reason (á½¡Ï‚ Ïƒá¿´Î¶Î¿Ï…ÏƒÎ±Î½ Ï„á½´Î½ Ï†ÏÏŒÎ½Î·ÏƒÎ¹Î½). This hypothesis would explain why Aristotle seems to engage in apotreptic language to characterize the lack of temperance, that is, the vice of intemperance (á¼€ÎºÎ¿Î»Î±ÏƒÎ¯Î±) ”“ something we do not find the in the account of any other virtue and vice.